How unhealthy commodity industries find a global audience in the English Premier League: three case studies of brand engagement. (4th July 2022) - Ireland, Robin; Bunn, Christopher; Chambers, Stephanie; Reith, Gerda; Viggars, Michael
ABSTRACT: Establishing the English Premier League has resulted in a dramatic rise in commercial activities, raising public health concerns around unhealthy brand marketing. The present paper deals with three linked case studies analysing the marketing techniques of three of the Premier League's partners in the 2019/20 season: Coca-Cola, Budweiser, and Cadbury. Data from Twitter were triangulated with promotional materials, product promotions in supermarkets and grey literature. An inductive thematic analysis explored the strategies used to engage fans. The studies show sponsors purchasing access to fans and inserting their brands into the emotional and passionate environment of EPL football. Sponsors evoke cultural traditions to align with and engage fans, to encourage consumption. Consumption is 'responsibilised' and positioned as an individual choice. The marketing techniques identified exploit social and cultural dimensions of EPL football to increase consumption of unhealthy brands, with the potential to negatively impact on the health of the EPL's audience.